2006
DOI: 10.1002/j.1551-8833.2006.tb07757.x
|View full text |Cite
|
Sign up to set email alerts
|

Economies of scale in community water systems

Abstract: Data sets from the U.S. Environmental Protection Agency's 1995 and 2000 Community Water Systems surveys were used to examine the production costs of water supply systems. The authors estimate water supply economies of scale by estimating the elasticities of both the total unit cost and the individual component costs. For total unit cost, they found that a 1% production increase reduced unit costs by a statistically significant 0.16%. For individual component costs, higher economies of scale in capital, materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 7 publications
3
54
0
Order By: Relevance
“…For the US, as in the two previous decades, strong economies of scale were found (Bhattacharya et al, 1994;Shih et al 2006). However, Torres and Morrison Paul (2006) observed economies of scale for small utilities but diseconomies of scale for the largest utilities.…”
Section: Lessons From Literature: a Short Surveymentioning
confidence: 77%
“…For the US, as in the two previous decades, strong economies of scale were found (Bhattacharya et al, 1994;Shih et al 2006). However, Torres and Morrison Paul (2006) observed economies of scale for small utilities but diseconomies of scale for the largest utilities.…”
Section: Lessons From Literature: a Short Surveymentioning
confidence: 77%
“…Using data collected from the American Water Workers Association, a number of studies that implemented either parametric or non-parametric techniques failed to ascertain whether private operators are more efficient than public ones. For instance, Mann and Mikesell [20] found that private operator owned utilities had higher costs than government utilities, and findings from many empirical studies support the idea that public providers are more efficient than private ones [21][22][23]. However, a different stream of studies showed that-on the contrary-public operators are less efficient, having higher costs than private ones [15,24,25].…”
Section: Private Vs Public Ownership And/or Management Of Water Provmentioning
confidence: 99%
“…Most studies confirm the presence of economies of scale in the water industry [11][12][13], but others highlight diseconomies of scale in various countries [14][15][16][17][18][19][20].…”
Section: Literature Reviewmentioning
confidence: 99%